Chapter Il degrado della biosfera - Bellanca, Nicolò (Studi e saggi, 2020)
The position of man in the biosphere and the interaction of its activities with the different sectors of the earth's ecosphere are bringing the Earth system into a drastically different state from that in which the development of advanced civilizations was possible.